como resolver as seguintes equações:
A) 10-2(Y+1)+3(2-Y)=Y+1
B)8-(X+3)-(2X-1)=X+7
Por favor, responda!
Soluções para a tarefa
Respondido por
2
Temos que:
a)![10-2(y+1)+3(2-y)=y+1 10-2(y+1)+3(2-y)=y+1](https://tex.z-dn.net/?f=10-2%28y%2B1%29%2B3%282-y%29%3Dy%2B1)
Assim,
,
ou seja,
.
Logo,
e ![y=\dfrac{13}{6} y=\dfrac{13}{6}](https://tex.z-dn.net/?f=y%3D%5Cdfrac%7B13%7D%7B6%7D)
b)![8-(x+3)-(2x-1)=x+7 8-(x+3)-(2x-1)=x+7](https://tex.z-dn.net/?f=8-%28x%2B3%29-%282x-1%29%3Dx%2B7)
![8-x-3-2x+1=x+7 8-x-3-2x+1=x+7](https://tex.z-dn.net/?f=8-x-3-2x%2B1%3Dx%2B7)
![x+2x+x=8-3+1-7 x+2x+x=8-3+1-7](https://tex.z-dn.net/?f=x%2B2x%2Bx%3D8-3%2B1-7)
Logo,
e
.
a)
Assim,
ou seja,
Logo,
b)
Logo,
erosrian:
muito obrigado paulo
Respondido por
1
A ) 10 - 2 ( y + 1 ) + 3 ( 2 - y ) = y + 1
10 - 2y - 2 + 6 - 3y = y + 1
- 2y - 3y - y = 1 - 10 + 2 - 6
- 6y = - 13 . ( - 1 )
6y = 13
y = 13/6 ou 2,16
B ) 8 - ( x + 3 ) - ( 2x - 1 ) = x + 7
8 - x - 3 - 2x + 1 = x + 7
- x - 2x - x = 7 - 8 + 3 - 1
- 4x = 1 . ( - 1 )
4x = - 1
x = - 1/4 ou 2,5 .
10 - 2y - 2 + 6 - 3y = y + 1
- 2y - 3y - y = 1 - 10 + 2 - 6
- 6y = - 13 . ( - 1 )
6y = 13
y = 13/6 ou 2,16
B ) 8 - ( x + 3 ) - ( 2x - 1 ) = x + 7
8 - x - 3 - 2x + 1 = x + 7
- x - 2x - x = 7 - 8 + 3 - 1
- 4x = 1 . ( - 1 )
4x = - 1
x = - 1/4 ou 2,5 .
Perguntas interessantes
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Geografia,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Psicologia,
1 ano atrás